Trouble in Queenstown - Pitts, Delia C., 1950- (Minotaur Books, 2024)
"With Trouble in Queenstown, Delia Pitts introduces private investigator Vandy Myrick in a powerful mystery that blends grief, class, race, and family with thrilling results. Evander "Vandy" Myrick became a cop to fulfill her father's expectations. After her world cratered, she became a private eye to satisfy her own. Now she's back in Queenstown, New Jersey, her childhood home, in search of solace and recovery. It's a small community of nine thousand souls crammed into twelve square miles, fenced by cornfields, warehouses, pharma labs, and tract housing. As a Black woman, privacy is hard to come by in "Q-Town," and worth guarding. For Vandy, that means working plenty of divorce cases. They're nasty, lucrative, and fun in an unwholesome way. To keep the cash flowing and expand her local contacts, Vandy agrees to take on a new client, the mayor's nephew, Leo Hannah. Leo wants Vandy to tail his wife to uncover evidence for a divorce suit. At first the surveillance job seems routine, but Vandy soon realizes there's trouble beneath the bland surface of the case when a racially charged murder with connections to the Hannah family rocks Q-Town. Fingers point. Clients appear. Opposition to the inquiry hardens. And Vandy's sight lines begin to blur as her determination to uncover the truth deepens. She's a minor league PI with few friends and no resources. Logic pegs her chances of solving the case between slim and hell no. But logic isn't her strong suit. Vandy won't back off"--